Communicating human biomonitoring results to ensure policy coherence with public health recommendations: analysing breastmilk whilst protecting, promoting and supporting breastfeeding - Arendt Maryse (BMC, 2008)
Abstract This article addresses the problem of how to ensure consistency in messages communicating public health recommendations on environmental health and on child health. The World Health Organization states that the protection, promotion and support of breastfeeding rank among the most effective interventions to improve child survival. International public health policy recommends exclusive breastfeeding for six months, followed by continued breastfeeding with the addition of safe and adequate complementary foods for two years and beyond. Biomonitoring of breastmilk is used as an indicator of environmental pollution ending up in mankind. This article will therefore present the biomonitoring results of concentrations of residues in breastmilk in a wider context. These results are the mirror that reflects the chemical substances accumulated in the bodies of both men and women in the course of a lifetime. The accumulated substances in our bodies may have an effect on male or female reproductive cells; they are present in the womb, directly affecting the environment of the fragile developing foetus; they are also present in breastmilk. Evidence of man-made chemical residues in breastmilk can provide a shock tactic to push for stronger laws to protect the environment. However, messages about chemicals detected in breastmilk can become dramatized by the media and cause a backlash against breastfeeding, thus contradicting the public health messages issued by the World Health Organization. Analyses of breastmilk show the presence of important nutritional components and live protective factors active in building up the immune system, in gastro intestinal maturation, in immune defence and in providing antiviral, antiparasitic and antibacterial activity. Through cohort studies researchers in environmental health have concluded that long-term breastfeeding counterbalances the effect of prenatal exposure to chemicals causing delay in mental and psychomotor development. Therefore caution should be exercised when presenting the results of biomonitoring of breastmilk. The results should be a motivation to enact strong legislation on chemicals and review the use of chemical substances present in breastmilk, but the results should not be used to undermine the confidence in breastmilk as the optimal food for infants and young children.